The Influence Of Implementing The Diverse, Nutritious, And Safe Program (Dnbs) On The Members Of The Family Welfare Program Working Group 3 (Pokja 3) In Surakarta - Suswadi; Asfuri, Ninda Beny; Santoso, Aan Budi (Journal of Rural and Urban Community Studies, 2023)
This study aims 1) to determine the influence of the cognitive aspects of PKK Surakarta City women before treatment and after treatment regarding the DNBS program, 2) To determine the effect of the attitude aspects of PKK Surakarta City women before treatment and after treatment regarding the DNBS program , 3) To determine the effect of cognitive abilities on the results of the healthy food competition for PKK Surakarta City Women This type of research is a quantitative study using a quasi-experimental design with one group pre-test and post-test design. The research subjects were PKK Surakarta women, totaling 30 people. Sampling was carried out using purposive sampling technique. Methods of data collection with pre-test or initial test, implementation of the treatment (treatment), and post-test or final test to collect final data. Data collection included data on the knowledge, attitude and psychomotor aspects of PKK Surakarta City women which were collected using tests for cognitive aspects, questionnaires for attitude aspects and competitions to see psychomotor aspects. The data collection instruments used were tests and questionnaires. The statistical analysis method used is simple regression analysis with the condition that the data distribution is normally distributed and the variables are homogeneous. Test the hypothesis using the t test. The results showed that 1) Based on the hypothesis test using the t-test showed that the sig. (2-tailed) <0.05 which means that there is a significant effect between the training provided on the cognitive abilities of the DNBS group (H1) is accepted, 2) Based on the hypothesis test using the t-test shows that the sig. (2-tailed) < 0.05. Test the hypothesis which states that there is a significant effect between the training provided on the attitude aspects of the DNBS group (H1) is accepted, 3)